New onset adrenal insufficiency in a patient with COVID-19. Issue 1 (18th January 2021) - Hashim, Maram; Athar, Syed; Gaba, Waqar Haider
Abstract : SARS-CoV-2 is the cause of COVID-19. Since the outbreak and rapid spread of COVID-19, it has been apparent that the disease is having multi-organ system involvement. Still its effect in the endocrine system is not fully clear and data on cortisol dynamics in patients with COVID-19 are not yet available. SARS-CoV-2 can knock down the host's cortisol stress response. Here we present a case of a 51-year-old man vomiting for 10 days after having confirmed COVID-19 infection. He had hypotension and significant hyponatraemia. Work-up was done including adrenocorticotropic hormone stimulation test. He was diagnosed as suffering from adrenal insufficiency and started on steroids with subsequent improvement in both blood pressure and sodium level. COVID-19 can cause adrenal insufficiency. Clinicians must be vigilant about the possibility of an underlying relative cortisol deficiency in patients with COVID-19.